Impact of a quality programme on overindication of surgeries for endometriosis and cholecystectomies - Otavio Berwanger; Miguel Cendoroglo Neto; Sidney Klajner; Mauro Dirlando Conte de Oliveira; Haggeas da Silveira Fernandes; Ana Luiz Vasconcelos; Fernanda Aparecida de Paula Russo; Daniel Tavares Malheiro; Giancarlo Colombo; Paula Pelegrini; Vanessa Teich; Alexandre Marra; et al. (BMJ Open Quality, 2023)
Approximately 45% of patients receive medical services with minimal or no benefit (low-value care). In addition to the increasing costs to the health system, performing invasive procedures without an indication poses a potentially preventable risk to patient safety. This study aimed to determine whether a managed quality improvement programme could prevent cholecystectomy and surgery for endometriosis treatment with minimal or no benefit to patients.This before-and-after study was conducted at a private hospital in São Paulo, Brazil, which has a main medical remuneration model of fee for service. All patients who underwent cholecystectomy or surgery for endometriosis between 1 August 2020 and 31 May 2021 were evaluated.The intervention consisted of allowing the performance of procedures that met previously defined criteria or for which the indications were validated by a board of experts.A total of 430 patients were included in this analysis. The programme prevented the unnecessary performance of 13% of cholecystectomies (p=0.0001) and 22.2% (p=0.0006) of surgeries for the treatment of endometriosis. This resulted in an estimated annual cost reduction to the health system of US$466 094.93.In a hospital with a private practice and fee-for-service medical remuneration, the definition of clear criteria for indicating surgery and the analysis of cases that did not meet these criteria by a board of reputable experts at the institution resulted in a statistically significant reduction in low-value cholecystectomies and endometriosis surgeries.